MENGULIK FAKTOR-FAKTOR PENYEBAB PASIEN GANGGUAN JIWA DI YAYASAN VILLA PEMULIHAN PELITA (POIMEN Jurnal Pastoral Konseling, 2023)
Mental disorders are a serious problem in this world, because mental disorders can prevent someone who experiences them from carrying out actions in social society. Even though there is modern understanding and treatment of mental disorders, there are still many people and even Christians who associate mental disorders with possession by evil spirits. This can trigger stigma towards people suffering from mental disorders and hinder their access to appropriate medical care. Article 3 of the Republic of Indonesia Constitution Number 18 of 2014 reads "providing health services in an integrated, comprehensive and sustainable manner through promotive, proven, curative and rehabilitative for ODMK and ODGJ”. Therefore, this research aims to answer the stigma circulating in society regarding people with mental disorders caused by evil spirits. The problem formulation of this research is what factors cause mental disorders in patients at the Villa Recovery Foundation. To answer the research problem, the researcher used a qualitative descriptive method, using interview techniques and library research in data collection. The results obtained from this research show that the factors that cause mental disorder patients at the Pelita Recovery Villa Foundation are not always caused by the public stigma about mental disorders being caused by evil spirits, but rather there are other factors.